Bahasa Bugis dalam perspektif Islam pada mahasiswa Sulawesi di D.I. Yogyakarta - Suleman, Muh. Asharif; Basri, Basri; Idayanti, Zulfi (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
Indonesian is part of the Austronesian language family and has a unique script system known as Lontara. Although Indonesian is more dominant, the Bugis language still plays an important role in maintaining the cultural identity and traditions of the Bugis people. This study was conducted to find differences in Bugis speech between students from Southeast Sulawesi in Yogyakarta and their home regions. The object of this research is 22 Southeast Sulawesi students who live in a student dormitory in Yogyakarta. A qualitative-descriptive approach based on Lev Vygotsky's theory was used in this study. The results show that dialectal variations, different ethnic backgrounds, historical and cultural factors, the use of Arabic letters in Bugis writing, the level of formality of use, and the development of Bugis language literature cause the differences in language speech. The findings highlight the importance of Bugis language preservation by Sulawesi students and the strengthening of the community's cultural identity, provide a new contribution to the development of literature on Bugis language development, especially in the Yogyakarta area, and provide new insights into efforts to preserve Indonesian culture.